2008
DOI: 10.1007/s00421-008-0797-4
|View full text |Cite
|
Sign up to set email alerts
|

The acute post-exercise response of blood pressure varies with time of day

Abstract: The reactivity of ambulatory blood pressure following a given change in everyday physical activities is highest in the morning. Whether the acute response of blood pressure following a controlled bout of steady-state exercise is influenced by time of day is examined in this study. After 45 min of supine rest, 12 male normotensives completed 30 min of cycling at 70% VO(2peak) which began at either 0800 or 1600 hours. Arterial blood pressure, cardiac output, total peripheral resistance, cutaneous blood flow and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
55
1
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 34 publications
6
55
1
12
Order By: Relevance
“…2 The lack of a BP reduction after the 1 脗 30-min exercise session could be due to inconsistent PEH responses in normotensives or to exercise timing. 2,10,11 Although PEH has been observed in normotensives immediately after exercise, 2 lower BP throughout the day after a morning exercise session was observed in hypertensives, but not in normotensives. 10 In fact, preexercise resting BP is a significant predictor of PEH.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…2 The lack of a BP reduction after the 1 脗 30-min exercise session could be due to inconsistent PEH responses in normotensives or to exercise timing. 2,10,11 Although PEH has been observed in normotensives immediately after exercise, 2 lower BP throughout the day after a morning exercise session was observed in hypertensives, but not in normotensives. 10 In fact, preexercise resting BP is a significant predictor of PEH.…”
mentioning
confidence: 97%
“…11 In addition, Jones et al 12 reported a greater postexercise arterial luminal shear rate and blood velocity after morning vs afternoon exercise, which was associated with differences in PEH. 11 This may explain why we observed reduced SBP only after the second and third 10-min exercise sessions (Figure 1). Body posture during BP measurements was not rigorously controlled, although subjects were always either seated or semi-recumbent in a hospital bed during BP measurements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with recent data from crossover-type experiments that indicated the presence of diurnal variation in the acute BP response after continuous exercise. [36][37][38] A consistent finding is that the reduction in MAP from baseline is greater when exercise begins in the afternoon compared with the early morning. The higher post-exercise MAP in the morning is consistent with the well-documented morning surge in BP implicated in the morning peak incidence of cardiac events.…”
Section: Discussionmentioning
confidence: 77%
“…39,40 It would appear that diurnal variation in post-exercise total peripheral resistance is important in explaining the higher BP after morning exercise. 36 Time of day effects on PEH may also help to explain some of the discrepancies in findings between previous studies.…”
Section: Discussionmentioning
confidence: 94%